Strategy for Abolishing Barriers to Women Participation in Labor Force - Gunawan, Tendy (Yayasan Jurnal Perempuan, 2021)
The female labor force participation rate has not moved from 50-55% in the last ten years, and this condition has been exacerbated by the covid-19 pandemic. This study looks at the various challenges for women in entering the world of work, maintaining jobs and building careers, and what strategies stakeholders can take to remove various barriers to women's labor force participation. The strategic recommendations include affirmative actions and policies that could be taken by policy makers and companies to remove barriers to women's participation in the workforce. The study is based on literature reviews of various studies and surveys conducted by the ILO in 2010-2020, especially regarding women in the world of work.